A Case of Cerebral Sinus Venous Thrombosis Resulting in Mortality in Severe Preeclamptic Pregnant Woman - Hatice Ender Soydinc; Ali Ozler; Mehmet Sıddık Evsen; Muhammet Erdal Sak; Abdulkadir Turgut; Serdar Basaranoglu; Abdurrahim Dusak; Mehmet Guli Cetincakmak (Hindawi Limited, 2013)
Cerebral venous sinus thrombosis (CVST) is a rarely encountered condition during pregnancy. A 21-year-old pregnant woman with labour pains was hospitalized in our clinic. Diagnosis of severe preeclampsia was made based on her clinical and laboratory findings. She suffered from convulsive episodes during postpartum period which lead to initiation of treatment for eclampsia. However neurological and radiological examinations were performed after emergence of additional neurological symptoms disclosed the diagnosis of CVST. In this paper, we aimed to present a case with CVST which diagnosis was confused with eclampsia and resulting in maternal mortality.